Three new species of Seira Lubbock (Collembola, Entomobryidae, Seirinae) from Madagascar with Lepidocyrtus-like habitus - Cipola, Nikolas Gioia; de Morais, José Wellington; Bellini, Bruno Cavalcante (Zootaxa, 2018)
Here three new species of Seira from Madagascar are described and illustrated, all with Lepidocyrtus-like habitus, as short antennae, truncate unguiculus, and overall reduction of dorsal macrochaetae. The new species Seira lepidochaetosa sp. nov., Seira semicaerulea sp. nov. and Seira metafemurata sp. nov. can be distinguished from each other by color patterns and chaetotaxic elements. An identification key for these three species is also provided, including a discussion on truncate unguiculus on Seira species with dense and reduced macrochaetotaxy.